Nephropathy and Encephalopathy in an Indonesian Patient with Dengue Viral Infection - Rachmadi, Dedi; Anggara, Mohamad Yanuar (International Journal of Integrated Health Sciences, 2013)
Objective: To describe unusual manifestation of dengue virus infection that has been increasing in number and elucidate the indirect effect of dengue infection on the central nervous system which may explain the occurence of dengue encephalopathy. Methods: A case report of 6-year-old boy who was admitted with a history of fever for three days, accompanied with decreased consciousness, hypertension, and edema is presented. Laboratory examination showed hemoconcentration, thrombocytopenia, with positive anti dengue Immunoglobulin G (IgG) and IgM, microscopic glomerular hematuria, and proteinuria as well as normal creatinine serum level. He was treated with supportive treatment. Results: After six days, the consciousness was improved and blood pressure was normal.  Proteinuia was alleviated by Day 11 and completely negative on Day 19.  Microscopic glomerular hematuria was negative after 6 months.Conclusions: Recognition of unusual dengue manifestations is important in early diagnosis and effective treatment of the disease.Keywords: Dengue virus infection, encephalopathy, nephropathy DOI: 10.15850/ijihs.v1n1.108